Heterogeneous Interactions During Bubble–Oil Droplet Contact in Water - Tao Yang; Hao Xiao; Chunyu Jiang; Ming Ma; Guangwen Zhang; Chun Wang; Yi Zheng; Xiangdi Zhao (Separations, 2025)
Oily wastewater is extensively generated during the petroleum extraction and refining processes, as crude oil production water and from the effluent systems in petrochemical enterprises. The discharge standards for such wastewater are stringent, with the Oslo–Paris Convention stipulating that the oil content must be below 30 mg/L for permissible discharge. Flotation, a conventional oil–water separation method, relies on the collision and adhesion of rising bubbles with oil droplets in water to form low-density aggregates that float to the surface for separation. The collision and adhesion mechanisms between bubbles and oil droplets are fundamental to this process. However, systematic studies on their interactions remain scarce. This study employs the extended Derjaguin–Landau–Verwey–Overbeek theory to analyze the three mechanical interactions during the collision–adhesion process theoretically and investigates the heterogeneous interaction dynamics experimentally. Furthermore, given the diverse liquid-phase environments of oily wastewater, the effects of salinity, pH, and surfactant concentration are decoupled and individually explored to clarify their underlying mechanisms. Finally, a solution is proposed to enhance the flotation efficiency fundamentally. This work systematically elucidates the influence of liquid-phase environments on the adhesion behavior for the first time through the unification of theoretical and experimental approaches. The findings provide critical insights for advancing flotation theory and guiding the development of novel coagulants.